(adsbygoogle = window.adsbygoogle || []).push({}); 1. The problem statement, all variables and given/known data

(3p^-3 q^-1)^2 x (-4p^3 q^-2)^2 = ?

Leave answer in positive indices

2. Relevant equations

3. The attempt at a solution

(3p^-3 q^-1)^2 x (-4p^3 q^-2)^2 = (9p^-6 q^-2)(16p^6 q^-4)

= 144q^-6

= 144/q^6

Is my answer correct or I am missing a concept? Thank you for taking the time to read.

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# (3p^-3 q^-1)^2 x (-4p^3 q^-2)^2 = ?

**Physics Forums | Science Articles, Homework Help, Discussion**